FACTORS AFFECTING UNDER-FREE VISITS TO POSYANDU IN THE WORKING AREA OF TELAGA DEWA PUSKESMAS BENGKULU CITY - Elly Wahyuni; Shelly Dwi Lestari; Sri Yanniarti (Poltekkes Kemenkes Bengkulu, 2023)
Posyandu is a form of Community-Based Health Efforts (UKBM) that is managed and organized by, from and with the community to empower and provide convenience to the community in obtaining health services for mothers, babies and toddlers. Based on Restra data for 2020, the national achievement target for carrying out regular weighing at posyandu is 88% in Indonesia. Meanwhile, the percentage of toddlers monitored for growth and development in Indonesia in 2021 is 69%. This study aims to determine the factors that influence the visit of toddlers to posyandu. This type of research is an analytic survey using a cross sectional approach. The population of this study were all mothers who had children aged 0-59 months in the working area of the Telaga Dewa Health Center. Sampling in this study using accidental sampling technique with a total sample of 98 respondents. This study used a research instrument in the form of a knowledge questionnaire. The results of this study indicate that there is a relationship between age, education, occupation, knowledge of toddler visits to posyandu. Dih a r a p k a n for p a r a mother who has a toddler by routine visits by toddlers to posyandu.